Greenwashing – The Dark Side of Eco-Friendly Marketing. A Case Study from Slovakia - Andrea Seberíni; Katarína Izáková; Miroslava Tokovská (Studia Ecologiae et Bioethicae)
Greenwashing is the practice of making false or misleading claims about the environmental benefits of a product or service. The purpose of this study is to examine consumers’ perceptions and experiences in relation to the greenwashing tactics used by Slovak businesses within the framework of environmental health policy. In the present study, we used data obtained through an inductive qualitative research design according to consolidated criteria. From 14 participants aged 20-45, using reflexive thematic analysis, we analysed three semi-structured focus group interviews. Four descriptive themes were created: (1) Individual and interpersonal determinants of consumers; (2) Marketing and organisational determinants of brands; (3) Public policy of the environment and health of the Slovak Republic; and (4) Environmental sustainability and ecological protection. The findings of our study confirmed that greenwashing often relies on buzzwords to reel in consumers, making them believe that the products they purchase are biodegradable or ethically sourced. The observed deterioration of consumer trust in product brands as a reaction to greenwashing threatens the potential of green marketing and contributes to damaging the reputation of the producers. One solution could be disseminating information on how customers can verify the authenticity of organic products through public and social media.